Answer:
- x-intercept will be: (-4, 0)
- y-intercept will be: (0, 2)
Explanation:
Given the equation
![3x\:-\:6y\:=\:-12](https://img.qammunity.org/2021/formulas/mathematics/college/f52u2gpxqn00a8yhx24v2yrtp9hrwh7jrr.png)
We know that x-intercept is obtained when we put y = 0,
so
![3x\:-\:6y\:=\:-12](https://img.qammunity.org/2021/formulas/mathematics/college/f52u2gpxqn00a8yhx24v2yrtp9hrwh7jrr.png)
3x - 6(0) = -12
3x = -12
x = -4
Therefore, x-intercept will be: (-4, 0)
We know that y-intercept is obtained when we put x = 0,
![3x\:-\:6y\:=\:-12](https://img.qammunity.org/2021/formulas/mathematics/college/f52u2gpxqn00a8yhx24v2yrtp9hrwh7jrr.png)
3(0) - 6y = -12
-6y = -12
y = 2
Therefore, y-intercept will be: (0, 2)